Persepsi Dosen Universitas Islam Kalimantan Muhammad Arsyad Al Banjari Terhadap Produk Makanan Berlabel Halal - Iman Setya Budi; Parman Komarudin (Wahana Islamika: Jurnal Studi Keislaman, 2020)
Food is everyone's need to fulfill their daily needs. Halal products are a person's choice in consuming food. The inclusion of halal labels on each product aims to provide certainty of the halal status of the product and to appease consumers, especially Muslim consumers, about the procedures, raw materials, and processing of the product itself. Halal label itself can be interpreted as information about a product that has been allowed to be consumed according to Islam. In Islamic teachings, a Muslim is taught to eat halal food. Islam forbids consuming pork, alcohol, blood, dead meat and meat that is not slaughtered according to Islamic law. The absence of a label on a product will make Muslim consumers to be careful in deciding the consumption of these products. Halal label on product packaging in Indonesia is a logo composed of Arabic letters that form the word halal in a circle. Thus, consumers can obtain a little information that can help them determine the halal nature of a product. This research aims to determine the perception of Kalimantan Islamic University Lecturer Muhammad Arsyad Al Banjari (UNISKA MAB) on Halal Label. This study used descriptive qualitative method. In collecting data using observation techniques, questionnaires and documentation. The subjects of the study were 50 lecturers from Kalimantan Islamic University Muhammad Arsyad Al Banjari (UNISKA MAB). The results of this study indicate that the perception of Kalimantan Islamic University lecturer Muhammad Arsyad Al Banjari (UNISKA MAB) of halal labeled products with a percentage rate of 53% strongly agrees or is important in choosing halal products and labels affect the interest in buying products with a percentage level of 72.34% .